2021
DOI: 10.4102/sajpsychiatry.v27i0.1602
|View full text |Cite
|
Sign up to set email alerts
|

The role of Mental Health Care Act status in dignity-related complaints by psychiatric inpatients: A cross-sectional analytical study

Abstract: Background: Globally interest has grown in promoting the rights of patients, especially psychiatric patients. Two core elements of patients’ rights are the rights to be treated in a dignified manner and to give feedback about services. Psychiatric patients may feel treated in an undignified manner, especially during involuntary hospital admissions.Aim: We explored the relationship between Mental Health Care Act 17 of 2002 (MHCA) status and dignity-related complaints.Setting: The study was conducted at a specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…We recommend that healthcare professionals engage with patients with the sensitivity needed to balance their vulnerability and dignity. This sensitivity will help to empower and support patients with mental ill health, similar to the study by Raphalalani et al (2021). In addition, our study indicates that families can be seen as a resource for a more person-centred care.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We recommend that healthcare professionals engage with patients with the sensitivity needed to balance their vulnerability and dignity. This sensitivity will help to empower and support patients with mental ill health, similar to the study by Raphalalani et al (2021). In addition, our study indicates that families can be seen as a resource for a more person-centred care.…”
Section: Discussionsupporting
confidence: 71%
“…A previous study points to dignity‐related matters being a common reason for the complaints of patients, particularly in involuntary patients with mental ill health (Raphalalani et al . 2021). More work is required to change attitudes and approaches related to dignity, the stigma, and discrimination of patients with mental ill health, and to address unmet mental healthcare needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involuntary admission is a common practice in SA ( 27 , 29 ), and a recent study from a psychiatric hospital in SA found that involuntary patients were more likely to have dignity-related complaints compared to voluntary patients ( 30 ). It is also important to prevent a negative involuntary admission experience because there is a suggestion that an involuntary admission does not necessarily have to bring about a feeling of coercion ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mental illness in South Africa was found to be highest in the African region, with the highest prevalence of chronic mental disorders among mental healthcare users (MH-CUs) [1,2]. Many MHCUs are treated as voluntary or involuntary inpatients in the hospital setting before being discharged to a primary health care or home environment [3]. Voluntary and involuntary acute mental healthcare users require short-term treatment therapy during hospitalisation until they are deemed to have recovered enough to be treated as an outpatient [4].…”
Section: Introductionmentioning
confidence: 99%